Systemic reflection on Informatics curriculum, models, and media in junior high school - Agung Arya Anggara (Himpunan Pengembang Kurikulum Indonesia, 2026)
The implementation of the Informatics curriculum at the junior high school level faces significant challenges in integrating technology with effective learning models. The gap between the demands of digital competency and relevant learning practices warrants a comprehensive evaluation. This study aims to conduct a systematic evaluation of the implementation of the Informatics curriculum, analyze the effectiveness of the applied learning model, and assess the use of technological media in the learning process in junior high schools. This study employed a qualitative case study approach at SMP Labschool UPI. Data were collected through structured classroom observations, in-depth interviews with two Informatics teachers, and a comprehensive analysis of learning documents, including lesson plans and teaching modules. Data analysis was conducted through systematic reduction, thematic categorization, and reflective interpretation to identify implementation patterns. The findings indicate that the curriculum is implemented in line with the national framework, with contextual variations in learning models tailored to student characteristics and resource availability. Project-Based Learning (PjBL) and collaborative learning are the most dominant pedagogical strategies. The use of technological media demonstrates adequate integration of hardware and software, despite limitations in access and technical skills. This study highlights the importance of developing more contextual learning strategies and enhancing educator capacity through ongoing professional development programs. Abstrak Implementasi kurikulum Informatika di tingkat Sekolah Menengah Pertama (SMP) menghadapi tantangan signifikan dalam mengintegrasikan teknologi dengan model pembelajaran yang efektif. Kesenjangan antara tuntutan kompetensi digital dan praktik pembelajaran yang relevan memerlukan evaluasi yang menyeluruh. Penelitian ini bertujuan untuk melakukan evaluasi sistemik terhadap implementasi kurikulum Informatika, menganalisis efektivitas model pembelajaran yang diterapkan, serta menilai pemanfaatan media teknologi dalam proses pembelajaran di SMP. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus di SMP Labschool UPI. Data dikumpulkan melalui observasi kelas terstruktur, wawancara mendalam dengan dua guru Informatika, serta analisis dokumen pembelajaran komprehensif yang mencakup rencana pelaksanaan pembelajaran dan modul ajar. Analisis data dilakukan melalui reduksi sistematis, kategorisasi tematik, dan interpretasi reflektif untuk mengidentifikasi pola implementasi. Temuan menunjukkan bahwa implementasi kurikulum mengikuti kerangka nasional, dengan variasi kontekstual dalam model pembelajaran yang disesuaikan dengan karakteristik murid dan ketersediaan sumber daya. Pembelajaran berbasis proyek dan pembelajaran kolaboratif menjadi strategi pedagogis yang paling dominan. Pemanfaatan media teknologi menunjukkan integrasi perangkat keras dan lunak yang memadai meskipun terdapat keterbatasan akses dan keterampilan teknis. Penelitian ini menyoroti pentingnya pengembangan strategi pembelajaran yang lebih kontekstual serta peningkatan kapasitas pendidik melalui program pengembangan profesional yang berkelanjutan. Kata Kunci: implementasi kurikulum; kurikulum Informatika; media dan model pembelajaran; teknologi pendidikan